An accurate ultrasonic wind speed and direction measuring method by combining time-difference and phase-difference measurement using coded pulses combination. (February 2020) - Jiang, Jia-jia; Dang, Wen-jie; Duan, Fa-jie; Wang, Xian-quan; Fu, Xiao; Li, Chun-yue; Sun, Zhong-bo; Liu, Han; Bu, Ling-ran
Abstract: In this paper, a high-precision and large-range wind speed and direction measuring method is proposed, which can solve the problem that traditional Time of Flight (ToF) method and phase detection method cannot simultaneously take into account measuring accuracy and measurement range. Firstly, based on the binary amplitude modulation and cross-correlation algorithms, the coded pulses combination is designed to measure time difference that the ultrasonic wave arrives different ultrasonic receivers. Because the coded pulses combination can obtain sharper correlation peaks, a more accurate time-difference measurement result can be gained, comparing with the traditional ToF method. Then, for further improving measuring accuracy and resolution of wind speed, a high-precision ±180° digital phase detection method based on double D flip-flops is proposed. Next, by combining time-difference and phase-difference measurement results, the measuring range of wind speed is extended and measuring accuracy is improved. Finally, a wind speed and direction measuring system is set up based on the proposed method. The experimental results show that the wind speed measuring accuracy is ±2%, the resolution is 0.05 m/s and the measurement range can theoretically reach several hundred meters per second; the wind direction measuring accuracy is ±5° and the resolution is 0.5°. At the same time, the standard deviations of the experimental results which are less than 10% demonstrate the stability of the system.